EVALUATION OF EUCALYPTUS KRAFT PULP LIGNIN THROUGH THE NITROBENZENE OXIDATION, COPPER OXIDE REDUCTION AND ACIDOLYSIS TECHNIQUES - Ventorim, Gustavo [UNESP]; Coelho, Alexandre [UNESP]; Colodette, Jorge Luiz; Alves, Ericka Figueiredo; Comelato, Jaqueline Silveira [UNESP] (Centro Pesquisas Florestais, Ufsm, 2014)
This study aimed to evaluate the sensitiveness of the information obtained for the residual lignin from Eucalyptus grandis kraft pulps analyzed through the nitrobenzene oxidation, copper oxide (CuO) reduction and acidolysis techniques. The chips were cooked, resulting pulps of kappa number 14,5 and 16,9, respectively. Both lignins' pulps were evaluated through three methods (nitrobenzene oxidation, copper oxide oxidation and acidolysis). Then, they were subjected to an oxygen delignification stage. The 16,9 kappa number pulp resulted in higher levels of non-condensed lignin structures by the acidolysis method, higher syringyl/vanillin ratios (S/V) by the nitrobenzene and copper oxide methods and better performance in the oxygen delignification stage. The different methods allowed to differ the residual lignin pulps with kappa number 14,5 and 16,9, and the nitrobenzene oxidation method showed the highest sensitiveness in this study results.
Keywords: residual lignin; nitrobenzene oxidation; acidolysis; copper oxide